Mechanics and applications of smart adhesive systems using shape memory polymers - Linghu, Changhong (Nanyang Technological University, 2023)
Smart adhesives – those that provide strong adhesion when needed and easy detachment as desired – are attracting intensive research interests recently and bringing about new opportunities in many fields ranging from daily usage like adhesive hooks to advanced technologies like end effectors for robotics. Insects and reptiles like geckos are experts of smart adhesives. With tiny and hierarchical adhesive fibrils on their toes, they can adhere to and run on various surfaces. Inspired by the smart fibrillar adhesives of insects and reptiles, many synthetic counterparts using elastomeric polymers have been developed and shown great potential in soft grippers, soft robotics, wearable electronics, medical tapes, and so on. However, these elastomeric smart adhesive systems are still limited in terms of adhesion strength, adhesion switchability, surface adaptability, and adhesion scalability on both the fibril and array levels. First, the typical adhesion strength of these elastomeric adhesives is on the order of 100 kPa, which makes their application impossible in large-payload conditions. Second, the elastomeric adhesives suffer from the long-standing challenges of the adhesion paradox (rapid decrease in adhesion strength on rough surfaces despite adhesive molecular interactions) and the switchability conflict (trade-off between adhesion strength and easy detachment). Third, bioinspired smart fibrillar adhesives have been limited by the scaling effect at the fibril/array level since developed in the early 2000s, resulting in a micro/nano-size of the adhesive fibrils with many challenges (e.g., difficulties in micro/nano-fabrication, susceptibility to bundling), and a limited exploitation efficiency (<26%) of an adhesive array’s full potential. In this thesis, we aim to address these challenges using shape memory polymers (SMPs). SMPs, with unique properties such as tunable elastic modulus, temporary shape locking, and shape recovery upon external stimulation, are emerging as a new class of smart materials with switchable adhesion capabilities.